Three-dimensional mapping of sternum fractures from high-energy trauma. - LaRoque, Michael C.; Obermeier, Michael C.; Cole, Peter A. (Journal of Trauma & Acute Care Surgery, 2022)
Background: Sternum fractures are relatively uncommon injuries, which generally occur as a result of a high-energy mechanism and are often associated with significant concomitant injuries. These injuries may result in decreased quality of life if not properly addressed and yet are rarely operated on. The purpose of this project is to evaluate high-energy sternum fracture patterns using a previously published three-dimensional (3D) computed tomography (CT) reconstruction process to produce fracture frequency maps.Methods: Patients 18 years and older presenting to a Level I trauma center with sternum fractures due to high-energy trauma between October 2013 and January 2022 were included. A 3D reconstruction and reduction was performed for each sternum using medical image processing software (Materialize NV, Leuven, Belgium). The reconstructions were subsequently overlaid onto a template sternum and normalized using bony landmarks. Fracture lines for each injured sternum were transferred onto the template, creating 3D frequency maps.Results: A total of 120 patients met inclusion criteria. The study population had a uniform age distribution and 57.5% were male. The most common mechanism of injury was motor vehicle collision (64.2%). The breakdown of sternum fractures were isolated sternal body (55.8%), isolated manubrium (31.7%), and combined sternal body and manubrium fractures (12.5%). No xiphoid fractures were observed. Sternal body fractures were a near even mix of transverse (31.7%), oblique (32.9%), and comminuted (35.4%), while 75.5% of manubrium fractures were oblique. The most common associated injuries included rib fractures (80.8%) and traumatic brain injury (61.7%).Conclusion: This study presents the fractures from sternum injuries in 3D, and provides insight into reproducible sternum injury patterns that have not previously been analyzed in this format. This fracture mapping technique presents numerous injury patterns simultaneously, such that more frequent morphologies can be appreciated for different patient groups.Level Of Evidence: Diagnostic Tests or Criteria; Level V.